Prinsip Keadilan dalam Pembiayaan Berbasis Financial Technology di Indonesia - Pasaribu , Jandiman Bernando; Sinaga, Niru Anita; Sudarto, Sudarto (Neolectura, 2025)
Financial Technology (Fintech) is an innovation in financial technology that offers practicality, ease of access, convenience, and cost efficiency. Its development has prompted the emergence of various regulations aimed at ensuring responsible and fair digital financial services. This study aims to examine the regulatory framework governing Fintech-based financing in Indonesia and how the principle of justice can be applied in its implementation. The research method used is normative juridical, by analyzing various laws and regulations, such as Law No. 8/1999 to POJK No. 10/POJK.5/2022. The findings show that although many regulations exist, there is still a need to strengthen legal protection, increase public awareness, and take firm actions against illegal Fintech providers. It is recommended that the government issue new regulations that explicitly incorporate the principle of justice in Fintech financing to ensure legal certainty, utility, and equal protection for all parties involved. The enforcement of justice principles requires collaboration between institutions, such as the Ministry of Communication and Information Technology (Kominfo) and the police (Polri), to supervise and regulate unlicensed Fintech services.